The Impact of Corporate Social Responsibility on the Growth of Basic Materials Sector Companies Listed on the Indonesian Stock Exchange - Fauzia, Fauzia; Patrisia, Dina (Universitas Negeri Padang, 2024)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) on the growth of basic materials sector companies listed on the Indonesia Stock Exchange (IDX). The population used in this study are all basic materials sector companies listed on the IDX for the period 2018-2022. The sample used in this study was determined by purposive sampling method, so that 71 companies were obtained with a total of 302 observations. This study uses secondary data in the form of annual reports (for CSR variables) and financial reports obtained from the official IDX website and each company. CSR measurement in this study uses an index measured based on a list of items that must be disclosed according to GRI Standards. The analysis method used is multiple linear regression analysis using SPSS 15.0. The results of this study indicate that 1) Corporate Social Responsibility (CSR) has a positive and significant effect on revenue growth, 2) Corporate Social Responsibility (CSR) has a positive and significant effect on total growth rate of assets.